Currency Undervaluation and Sovereign Wealth Funds: A New Role for the World Trade Organization - Mattoo, Aaditya; Subramanian, Arvind (2012)
Two aspects of global imbalances--undervalued exchange rates and sovereign wealth funds--require a multilateral response. For reasons of inadequate leverage and eroding legitimacy, the International Monetary Fund has not been effective in dealing with undervalued exchange rates. This paper proposes new rules in the World Trade Organization to discipline cases of significant undervaluation that are clearly attributable to government action. The rationale for WTO involvement is that there are large trade consequences of undervalued exchange rates, which act as both import tariffs and export subsidies, and that the WTO's enforcement mechanism is credible and effective. The World Trade Organization would not be involved in exchange rate management, and would not displace the International Monetary Fund. Rather, the authors suggest ways to harness the comparative advantage of the two institutions, with the International Monetary Fund providing the essential technical expertise in the World Trade Organization's enforcement process. There is a bargain to be struck between countries with sovereign wealth funds, which want secure and liberal access for their capital, and capital-importing countries, which have concerns about the objectives and operations of sovereign wealth funds. The World Trade Organization is the natural place to strike this bargain. Its General Agreement on Trade in Services already covers investments by sovereign wealth funds, and other agreements offer a precedent for designing disciplines for these funds. Placing exchange rates and sovereign wealth funds on the trade negotiating agenda may help revive the Doha Round by rekindling the interest of a wide variety of groups.